The Power Of Presidential Legislation After The Amendment of UUD 1945 - Suling, Moh. Sulfikar (VRISPRAAK : International Journal of Law, 2024)
This research is to analyze and understand the accordance of the presidential legislative power after the amendment of the UUD 1945 to the presidential system principles. This legal research used statute approach, conceptual, comparative, and historical. Primary and secondary legal materials used in this study were collected through literature which investigates and inventory the legal materials with documents, literature books, law journals, and legislation related to the object of research. Legal materials that have been obtained are described and presented descriptively and analytically deduced by using the deductive method. The results showed that the presidential legislative power after the amendment of the UUD 1945 is not in accordance with the principle of the presidential system of government explicitly separating the executive and legislative branches of power in the power system as an implementation of the idea of ??limiting state power and the principle of popular sovereignty. The presidential legislative power after the amendment of the UUD 1945 tends to weaken the legislative function, creates an imbalance between the executive and the legislature, and inhibit the realization of the legislation in accordance with the will of the people.